Pengaruh Inflasi, Suku Bunga, Profitabilitas, Solvabilitas Terhadap Harga Saham LQ45 yang Terdaftar di BEI Periode 2017-2021 - Sri Minari Faulianti; Dikdik Harjadi; Fauziyah Adzimatinur (Indonesian Journal of Strategic Management, 2023)
This study aims to determine how the effect of inflation, interest rates, profitability, and solvency on stock price of companies LQ45 listed on the IDX for the 2017-2021 period. The research population is taken from the annual financial statements of companies listed in the LQ45 index for the 2017-2021 period on the Indonesia Stock Exchange is 45 companies. The number of samples in this study consisted of 19 companies using a purposive sampling technique. Hypothesis testing using a panel data regression with Random Effect to model the statistics, using Eviews 10 in processing the data. Statistical analysis was used in this study namely panel data regression, for hypothesis testing, namely the F test and t test. Based on the results of the F test, it states that the Inflation, Interest Rate, Profitability (ROE), and Solvency (DER) have a positive effect on stock price of LQ45. The results of the t-test state that inflation has a positive and significant effect on stock prices. Meanwhile, interest rates, profitability, and solvency have no significant effect on stock prices.